PENGEMBANGAN VIRTUAL LABORATORY UNTUK PRAKTIKUM JARINGAN DASAR PADA HEWAN - Valisa, Viola Vinca; Suryawati, Evi; Arnentis, Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Biology education students are future teacher candidates who are required to be able to have various competencies, one of which is competence in carrying out practical activities. Practical activities can provide contextual experience in implementing existing theoretical studies. However, there are various obstacles to carrying out practical activities that can affect the content knowledge of prospective biology teacher students. This study aims to develop independent learning resources for prospective teacher students in the form of a virtual laboratory equipped with a practical guide book. This research was conducted at the Laboratory of PMIPA FKIP Riau University, SMAN 8 Pekanbaru, and SMAN 14 Pekanbaru in December 2020 – May 2021. It used a Research and Development (R&D) approach with ADDIE model. The instruments used are validation sheets and response questionnaires. The validation results obtained an average value of 3.62 (virtual laboratory) and 3.51 (guidebook) in the very valid category. The results of the limited trial phase I obtained an average value of 3.88 (virtual laboratory) and 3.96 (guidebook) in the very good category. The results of the limited trial phase II obtained an average value of 3.80 (virtual laboratory) and 3.86 (guide book) in the very good category. The results showed that the virtual laboratory and guide books that were developed is good quality and suitable to be used as independent learning resources to increase content knowledge for prospective teacher candidates.Key Words: Virtual Laboratory, Practical Guide, Animal Base Tissue